Aktivitas Fisik dan Status Gizi Mahasiswa Saat Pandemi COVID-19 - Supit, Enrico D.; Mayulu, Nelly; Bolang, Alexander S. L.; Kawengian, Shirley (Jurnal Biomedik : JBM, 2021)
Abstract: The imposition of social restrictions during the Covid-19 pandemic resulted in limitations in carrying out physical activities. Physical activity is a determining factor for a person's nutritional status by affecting body mass index (BMI). The purpose of this study was to determine the relationship between the metabolic equivalent (MET) and the body mass index (BMI) of Class 2017 Students for the Medical Education Study Program of the Faculty of Medicine Unsrat during the Covid-19 Pandemic and the relationship between physical activity and nutritional status based on Class 2017 Student Education Study Program Doctor of the Faculty of Medicine Unsrat during the Covid-19 Pandemic. The study used an analytical method with a cross-sectional approach to students of class 2017 of the medical education program at the Faculty of Medicine Unsrat during the Covid-19 pandemic with a total sample of 105 people. Data analysis and hypothesis testing were carried out using SPSS. Result. The significance value between metabolic equivalent (MET) and body mass index (BMI) was (p) 0.035 and the significance value between physical activity and nutritional status was (p) 0.069. In conclusion, Statistically, it was found that there was a significant relationship between metabolic equivalent (MET) and body mass index (BMI) (p) 0.035 <0.05 and there was no significant relationship between physical activity and nutritional status (p) 0.069> 0.05.Keywords: physical activity, nutritional status.Â Â Abstrak: Pemberlakuan pembatasan sosial selama pandemi Covid-19 menyebabkan keterbatasan dalam melakukan aktivitas-aktivitas fisik. Aktivitas fisik merupakan suatu faktor penentu status gizi seseorang dengan mempengaruhi indeks massa tubuh (IMT). Tujuan penelitian ini adalah, Mengetahui hubungan antara metabolic equivalent (MET) dengan indeks massa tubuh (IMT) Mahasiswa Angkatan 2017 Program Studi Pendidikan Dokter Fakultas Kedokteran Unsrat saat Pandemi Covid-19 dan hubungan antara aktivitas fisik dan status gizi berdasarkan Mahasiswa Angkatan 2017 Program Studi Pendidikan Dokter Fakultas Kedokteran Unsrat saat Pandemi Covid-19. Penelitian menggunakan metode analitik dengan pendekatan cross-sectional pada mahasiswa angkatan 2017 program studi pendidikan dokter Fakultas Kedokteran Unsrat saat pandemi Covid-19 dengan total sampel 105 orang. Analisis data dan uji hipotesis dilakukan dengan menggunakan SPSS. Hasil. Didapatkan nilai signifikansi antara metabolic equivalent (MET) dan indeks massa tubuh (IMT) sebesar (p) 0.035 dan diapatkan nilai signifikansi antara aktivitas fisik dan status gizi sebsesar (p) 0.069. Sebagai simpulan, secara satatistik didapatkan ada hubungan signifikan antara metabolic equivalent (MET) dan indeks massa tubuh (IMT) (p) 0.035 < 0.05 dan tidak ditemukan hubungan signifikan antara aktivitas fisik dan status gizi (p) 0.069 > 0.05.Kata Kunci: aktvitas fisik, status gizi.